Bromopyrogallol Red: A New Microanalytical Reagent for Amperometric Estimation of Dy(III) and Gd(III)† - Sahu, G.P.; Lavale, S.C. (Asian Journal of Chemistry, 2010)
Bromopyrogallol Red (BPR) has been extensively used as an indicator but its electro-reducibility has proved it to be a very useful amperometric reagent. BPR reduces on a DME in KNO3 in the entire pH range 2.4 to 9.5. It produces single stage reduction wave below pH 4, but a two stage reduction wave in the basic range. Progressive ionization of hydroxyl group and distinct colour species of BPR, have also been studied using a Bausch and Lomb spectronic-20 spectrophotometer in order to support electroanalytical studies. On performing amperometric titrations of Dy(III) and Gd(III) with BPR at its plateau potential 1.0 V at pH 2.6 and μ= 0.4, reversed L-shaped titration curves have been observed indicating metal to BPR ratio 1 : 1 and the colour changes from claret red to orange yellow. The reagents have been tested in presence of various diverse ions and tolerance limits have been computed. Na+, K+, Li+, Cl-, ClO4-, CH3COO-, Pd2+, Fe3+ ions did not interfere in the titrimetric Rrocedure. However, small amounts of Bi3+, Pb2+, Ni2+, CO2+, Cd2+, Mg2+ and rare earth metals have hampered the titrimetric estimations.